REVENUE DISTRIBUTION FROM FEDERATION ACCOUNT AND MONEY SUPPLY: EVIDENCE FROM NIGERIA - OMODERO, Cordelia Onyinyechi (Annals of Spiru Haret University. Economic Series, 2019)
Abstract Money supply in every economy is very vital for economic growth and stability. However, the role of revenue distribution in ensuring the success of monetary policies revolving around money supply in Nigeria cannot be over-estimated. The study examines the impact of revenue distribution to the three tiers of government on money supply (MSS) in Nigeria. Time series data used for the study estimation span from 1981-2016 and were obtained from CBN statistical bulletin, 2016 edition and World Bank website. The specific purpose of the study is to establish the extent to which revenue allocation to federal, state, local governments and derivation allowance to the mineral producing states affect money circulating in the Nigerian economy. Ordinary least square method (OLS) was employed with the aid of SPSS version 20 to test the impact of revenue distribution on money supply. The findings reveal that revenue allocation to federal government has a significant positive impact on money supply. Allocation to local government councils has insignificant positive impact on money supply. On the contrary, allocation to states and the derivation allowance to Niger Delta States exert significant negative influence on MSS in Nigeria. The study concludes that, revenue allocation to states and derivation allowance contribute to inflation in the country and recommended stringent monetary policies that will determine the percentage of allocated revenue usage by all tiers of government in a particular period to avoid too much money in circulation. Keywords: Revenue distribution, allocation, money supply, economic stability, derivation. JEL CODE: E51, E64.